From Enniskillen to Nairobi: The Coles in British East Africa - Patten, Eve (Palgrave Macmillan, 2019)
In the opening decades of the twentieth century a close connection was forged between Ireland and British East Africa (or the Colony and Protectorate of Kenya as it became in 1920) by three of the children of the fourth Earl of Enniskillen: Florence Cole (b. 1878), Galbraith Lowry Cole (b. 1881) and Reginald Berkeley Cole (b. 1882). All three were part of the pioneering settlement of the East African territory in the wake of the Boer War and through the course of the First World War—events which in turn served as portals to colonial land-purchase more widely across the African continent. During this period their letters to friends or home to Florence Court, the family’s ancestral seat in County Fermanagh, provide an intriguing portrait of these Ulster-born aristocrats and their participation in Britain’s colonial expansion and consolidation. The siblings also feature in literary accounts and memoirs of Kenya by Elspeth Huxley, Karen Blixen and various other authors who were their contemporaries in the formative years of the Protectorate.
Ireland's Imperial Connections, 1775--1947
Keywords: Identities in Transformation; Making Ireland; 20th century Ireland; British government in Ireland; Diaspora; Ireland and Africa since 1870; Ireland and Empire; Globalization; History; Literature